2008
DOI: 10.1080/08037050701758018
|View full text |Cite
|
Sign up to set email alerts
|

Self‐measurement of blood pressure at home: Is it reliable?

Abstract: Self-measurement of blood pressure (BP) at home is more common than 10 years ago and encouraged by current guidelines to increase patient adherence to treatment and reach the goal of target BP. The aims of this study are to evaluate the accuracy of home sphygmomanometers and to investigate behavior/knowledge of the sphygmomanometer owners. A campaign was planned to determine the accuracy of home sphygmomanometers in 2006. Seven hundred and twenty-three home sphygmomanometers were brought by individuals to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…To our knowledge, the accuracy of sphygmomanometers used at pharmacies has not been studied previously. Inaccuracy of sphygmomanometers is a common problem [24] . The frequency of inaccurate devices shows a wide variation, from 0 to 72% [24,25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the accuracy of sphygmomanometers used at pharmacies has not been studied previously. Inaccuracy of sphygmomanometers is a common problem [24] . The frequency of inaccurate devices shows a wide variation, from 0 to 72% [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies investigating inaccuracy of sphygmomanometers were conducted in hospital or primary care settings and a few number of studies investigated home sphygmomanometers [24] . Our study showed that 40 of the 135 (30%) devices were inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were informed about the campaign to evaluate the accuracy of BP measurements performed at home by using home sphygmomanometers through television programs, newspapers, patient meetings, brochures, and banners. We published our first findings recently [13]. As we did not collect the data regarding the manufacturer and models of the devices in the first study [13], we were unable to evaluate the validation of the sphygmomanometers.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the main questions were as follows: use and frequency of use of HBPM [15]; reasons for use and nonuse [16][17][18]; reliability of HBPM [19][20][21][22]; benefits of HBPM in everyday management of hypertensive patients [23,24]; limitations of HBPM [16,18,25,26]; HBPM contraindications [5]; practical modalities for the provision of devices [16,17]; type of devices and their validation [27]; number of devices owned by the physician [16,17]; HBPM measurement procedures [4,5]; use of written instructions given to the patient (patient education) [28]; and rough assessment or exact computation of the mean BP measurements [16].…”
Section: Main Questionsmentioning
confidence: 99%